2022
DOI: 10.3390/molecules27092927
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Biological Effects of Root-Filling Materials for Primary Teeth by Incorporating Sodium Iodide

Abstract: Therapeutic iodoform (CHI3) is commonly used as a root-filling material for primary teeth; however, the side effects of iodoform-containing materials, including early root resorption, have been reported. To overcome this problem, a water-soluble iodide (NaI)-incorporated root-filling material was developed. Calcium hydroxide, silicone oil, and NaI were incorporated in different weight proportions (30:30:X), and the resulting material was denoted DX (D5~D30), indicating the NaI content. As a control, iodoform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…The atomic number, density, and size of the chemicals in the root canal paste have a significant impact on how x-rays interact with matter at the atomic level [35,36]. Since sodium iodide (molecular weight 149.89 g/mol) has a lower atomic number than that of iodoform (393.732 g/mol), NaI paste showed the lowest radiopacity when compared to Vitapex® and Metapex®, which was consistent with a previous study [13]. However, there was no statistically significant difference among the groups.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The atomic number, density, and size of the chemicals in the root canal paste have a significant impact on how x-rays interact with matter at the atomic level [35,36]. Since sodium iodide (molecular weight 149.89 g/mol) has a lower atomic number than that of iodoform (393.732 g/mol), NaI paste showed the lowest radiopacity when compared to Vitapex® and Metapex®, which was consistent with a previous study [13]. However, there was no statistically significant difference among the groups.…”
Section: Discussionsupporting
confidence: 90%
“…However, NaI paste exhibited the highest antibacterial activity, suggesting that sodium iodide is a more effective bactericidal agent than iodoform. Although high antimicrobial activity can sometimes be associated with high cell toxicity, a study by Choi et al, found that NaI paste did not induce cell cytotoxicity, suggesting that it may be effective against bacteria within dentinal tubules without being toxic [13]. Nevertheless, this study was conducted in vitro over a short period of time, and further research is needed to validate these findings in vivo.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations